2019 Computing in Cardiology Conference (CinC) 2019
DOI: 10.22489/cinc.2019.318
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Heart Rate Variability Representations on the Quantification of the Cardiorespiratory Interactions

Abstract: The Heart Rate Variability (HRV) is a noninvasive tool to evaluate the activity of the autonomic nervous system. To study the HRV, different mathematical representations can be used. The selection of a representation might have an effect on the evaluation of the mechanisms that modulate the Heart Rate (HR). One of these mechanisms is the Respiratory Sinus Arrhythmia (RSA), i.e. an increased HR during inhalation and a decreased HR during exhalation. Different methods exist to quantify the RSA. A common approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In contrast, the work reported in [50] and the results presented in section III-B indicate that P HF is an overestimation of the cardiorespiratory coupling. According to the results in the simulation, this might indicate that the weight of modulations related to the respiration were stronger in [17] and [51], with a β R > 0.5. Another possible explanation is shown in Figure 11, which shows an example of the RSA estimation in a 5-minutes epoch taken from the sleep dataset.…”
Section: B Application To Real Datamentioning
confidence: 83%
See 1 more Smart Citation
“…In contrast, the work reported in [50] and the results presented in section III-B indicate that P HF is an overestimation of the cardiorespiratory coupling. According to the results in the simulation, this might indicate that the weight of modulations related to the respiration were stronger in [17] and [51], with a β R > 0.5. Another possible explanation is shown in Figure 11, which shows an example of the RSA estimation in a 5-minutes epoch taken from the sleep dataset.…”
Section: B Application To Real Datamentioning
confidence: 83%
“…At this point, two previous works can be discussed taking into account the results presented in III-B. In [17] and [51], it was shown that P HF underestimates the percentage of power explained by the respiration in the HRV. In both cases, the data was recorded in a controlled environment.…”
Section: B Application To Real Datamentioning
confidence: 94%